EUCOP4 Book of Abstracts - Gonçalo Vieira; Pedro Pina; Carla Mora; António Correia (Zenodo, 2014)
EUCOP4, the 4th European Conference on Permafrost and Regional Conference of the International Permafrost Association is hosted by the Portuguese Universities of Lisbon and Évora and is to be held in Évora from the 18th to the 21st June 2014. The conference provided the opportunity to bring together researchers from all over the world to present and discuss some of the most recent advances and results in permafrost and related subjects. More than 370 researchers from 24 countries have registered. A very positive response to the Call for Papers for EUCOP4 was obtained, with more than four hundred and fifty submissions. This book contains 425 abstracts, including those from the 3 plenary lectures, 1 from The Wiley-Blackwell Permafrost and Periglacial Processes Public Lecture and 23 session keynote lectures. The high quality of the scientific program is to be thanked to the authors and also to the chairs of the 23 thematic sessions, that made a fantastic work in their promotion and also in conducting all reviewing and selection procedures. We are very indebted to all of them. We are also very pleased to benefit from the participation of our guest speakers Prof Oleg Anisimov, State Hydrological Institute (Russia), Prof Frederick Nelson, Univ. Wisconsin (USA), Prof James Bockheim, Univ. Wisconsin-Madison (USA) and Prof Christian Hauck, Univ. Fribourg (Switzerland), for their plenary lectures. We are also very delighted to receive at EUCOP4 ‘The Wiley-Blackwell Permafrost and Periglacial Processes Public Lecture - PPP Award for Excellence in Permafrost Research’ by Prof. Chris Burn, Carleton University (Canada). We express our gratitude to these world renowned experts on permafrost. The International Scientific Committee has supported the Local Organizing Committee since an early stage in defining the science program and has provided timely comments on key questions on the organization. We are indebted to all members who accepted to support us. Special thanks are due to Toni Lewkowicz, Hanne H. Christiansen, Bernd ...